History of Science: Hospitals in the Golden Era of Muslim History - Haque, Anwar Ul (International Journal of Pathology, 2019)
(Disclaimer: This is not an original research article from IJP, this very informative piece of information is almost entirely taken from Wikipedia;https://en.wikipedia.org/wiki/Islamic_Golden_Age for which we thank Wikipedia and its contributors. We do not 100% agree what’s written here but weconsidered it quite useful and informative. We have serious objection on distortion of names of Muslim Scientists and their books as well as on notacknowledging some of the facts; for example it was not Christian translators who automatically translated their work into Arabic but it was Ma’moonRashid’s “House of Wisdom” which collected all the scientific work then present and carried out painstaking translation of all the work, analyzing itand rejecting what was wrong or unscientific and retained what was considered to be correct on scientific merit. Turning Ibn-e-Sina into Avicenna andtranslating his book as Canon of Medicine rather than “Law (Qa’noon) of Medicine” reflect ignorance and prejudice… Editors)